Arahan Konservasi DAS Meureudu Menggunakan Sistem Informasi Geografis (SIG) - Ummi Kalsum; Yuswar Yunus; T Ferijal (Fakultas Pertanian, Universitas Syiah Kuala, 2017)
Abstrak. Erosi dapat memicu degradasi lahan. Potensi erosi akan meningkat dengan semakin berkurangnya tutupan lahan dan minimnya tindakan konservasi. SIG diterapkan dalam berbagai ilmu antaranya yaitu dalam bidang bidang sumberdaya alam (inventarisasi manajemen dan kesesuaian lahan untuk pertanian). Rumusan masalahnya adalah sebagai berikut, Apakah kelas erosi yang terjadi di DAS Meureudu berada dalam kategori sedang ? Bagaimana penerapan upaya konservasi vegetatif dan mekanik ? Apakah terdapat korelasi antara besarnya erosi dengan upaya konservasinya ?. Kelas erosi yang terjadi di DAS Meureudu berada dalam kategori sedang. Upaya konservasi vegetatif dan mekanik di DAS Meureudu dapat diterapkan. Terdapat korelasi antara besarnya erosi yang terjadi di DAS Meureudu dengan upaya konservasinya. Jumlah erosi total yang terdapat di DAS Meureudu sebesar 109,52 ton/ha/thn, termasuk kedalam kelas laju erosi yang sedang. konservasi yang disarankan dapat mengurangi laju erosi yang terdapat di DAS Meureudu menjadi 24,62 ton/ha/thn. Penerapan konservasi dengan jenis tanaman dan pengelolaan yang tepat dapat mengurangi kelas laju erosi sedang menjadi ringan.Kata kunci : Erosi, SIG, KonservasiAbstract. Erosion triggers soil degradation and its rate will increase due to a decline topsoil quality with no real conservation. By using GIS (Geographic Information Systems) to examine the soil erosion and the conservation practices on the Drainage Basin (DAS) Meureudu.The formulation of the problem is as follows, Do class erosion in the watershed Meureudu in a category is? How the application of vegetative and mechanical conservation efforts? Whether there is a correlation between the magnitude of erosion by conservation efforts?. Class erosion in the watershed Meureudu are in the medium category. Vegetative and mechanical conservation efforts in the watershed Meureudu can be applied. There is a correlation between the magnitude of the erosion in the watershed Meureudu with conservation aims. it was found that the total erosion in that area was 109,52 ton/ha/year (categorized as average rate of soil erosion). Concerning this result, the conservation practices needed was 24,62 ton/ha/year. Applying appropriate conservation such as using proper management and plants will decrease the rate of soil erosion.Keywords: Erosion, GIS, ConservationAbstract. Erosion triggers soil degradation and its rate will increase due to a decline topsoil quality with no real conservation. By using GIS (Geographic Information Systems) to examine the soil erosion and the conservation practices on the Drainage Basin (DAS) Meureudu.The formulation of the problem is as follows, Do class erosion in the watershed Meureudu in a category is? How the application of vegetative and mechanical conservation efforts? Whether there is a correlation between the magnitude of erosion by conservation efforts?. Class erosion in the watershed Meureudu are in the medium category. Vegetative and mechanical conservation efforts in the watershed Meureudu can be applied. There is a correlation between the magnitude of the erosion in the watershed Meureudu with conservation aims. it was found that the total erosion in that area was 109,52 ton/ha/year (categorized as average rate of soil erosion). Concerning this result, the conservation practices needed was 24,62 ton/ha/year. Applying appropriate conservation such as using proper management and plants will decrease the rate of soil erosion